Socio-ecological perspectives of Himalayan Giant Nettle (Girardinia diversifolia (Link) Friis) in Nepal. Issue 1 (2nd January 2020) - Subedee, Bijay Raj; Chaudhary, Ram Prasad; Uprety, Yadav; Dorji, Tashi
ABSTRACT: Natural fibers have attracted considerable attention in recent years because of their low cost, renewable, and eco-friendly nature. The study investigated the economic, social, medicinal, and traditional use of Himalayan Giant Nettle commonly called "Allo" ( Girardinia diversifolia ) in Nepal. The fiber extracted from "Allo" is one of the income sources for people living in rural mountainous region of Nepal. The traditional fiber processing techniques, use of locally available materials, and medicinal value helped to preserve "Allo." Nevertheless, the resource stock is declining from its natural habitat due to changes in traditional grazing practices, rapid expansion of plantation of cash crops like large cardamom ( Amomum subulatum) and Chirayito ( Swertia chirayita) where "Allo" grows naturally. Cultivation, sustainable harvesting, and policy formulation on "one-door taxation" system are important to preserve this important natural fiber species.